2001
DOI: 10.1017/s0959774301000099
|View full text |Cite
|
Sign up to set email alerts
|

Interview with a Neanderthal: an Experimental Approach for Reconstructing Scraper Production Rules, and their Implications for Imposed Form in Middle Palaeolithic Tools

Abstract: This article investigates the degree and nature of ‘imposed form’ in Middle Palaeolithic scrapers, the most common category of stone tool produced by Neanderthals. Novice flintknappers unfamiliar with Middle Palaeolithic tool forms were found to consistently employ two rules in manufacturing scrapers: the striking platform and any adjacent blunt edges were left intact to facilitate prehension, and the longest edge with the most acute spine-plane angle was retouched. Scrapers from three major Middle Palaeolithi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…How are we to make sense of this? One of the longest‐standing debates in archaeology concerns the variation present in Paleolithic hide scrapers (Andrefsky 1994; Bamforth 1986; Bisson 2001; Bordes 1961; Dibble 1987; Kuhn 1992; Meltzer 1981; Wobst 2000), yet no one has suggested that perhaps differences in sex and gender may account for the stone‐scraper variability. The latter once again reflects the idea that archaeologists perceive women's technology as unskilled and expedient.…”
Section: Discussionmentioning
confidence: 99%
“…How are we to make sense of this? One of the longest‐standing debates in archaeology concerns the variation present in Paleolithic hide scrapers (Andrefsky 1994; Bamforth 1986; Bisson 2001; Bordes 1961; Dibble 1987; Kuhn 1992; Meltzer 1981; Wobst 2000), yet no one has suggested that perhaps differences in sex and gender may account for the stone‐scraper variability. The latter once again reflects the idea that archaeologists perceive women's technology as unskilled and expedient.…”
Section: Discussionmentioning
confidence: 99%
“…In the examples analyzed here we discovered that, as opposed to scrapers, in which flakes with long and regular edges to retouch are preferred (Bisson, 2001), the choice of the blank for the production of denticulates is not associated with a particular shape or size. The most significant feature is the intention to change the properties of the blank to create a denticulate outline with respect to the requirements of manual prehension.…”
Section: Discussionmentioning
confidence: 79%
“…Bisson, 2001;Bourguignon, 1997;Bourguignon et al, 2004;Thiébaut, 2003;Turq, 2000;Verjux, 1988;Verjux and Rousseau, 1986), reinforcing the possibility that flake form may have an important role in the construction of morphological diversity amongst Mousterian implements. Many discussions of flake-retouch relationships have posited a simple relationship between flake elongation and the position of retouch, suggesting that long flakes were often retouched on their lateral margins, whereas short, wide flakes were often worked at the distal end (e.g.…”
Section: The Question Of Quina Scrapers and Reductionmentioning
confidence: 99%